2009
DOI: 10.1016/j.mcna.2009.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to and Determinants of Medication Adherence in Hypertension Management: Perspective of the Cohort Study of Medication Adherence Among Older Adults

Abstract: Low adherence to antihypertensive medication remains a public health challenge. Understanding barriers to, and determinants of, adherence to antihypertensive medication adherence may help identify interventions to increase adherence and improve outcomes. The Cohort Study of Medication Adherence in Older Adults (CoSMO) is designed to assess risk factors for low antihypertensive medication adherence, explore differences across age, gender, and race subgroups, and determine the relationship of adherence with bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
240
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 202 publications
(263 citation statements)
references
References 70 publications
(57 reference statements)
15
240
0
7
Order By: Relevance
“…The attenuation in risk reduction was mainly attributed to the reclassification of 44% (n=20 735) of beneficiaries with intermediate adherence (40–79%) under ≥1 antihypertensive available PDC to ≥80% category using the first‐year PDC. Many studies suggested that the average medication adherence declined significantly over time with the greatest changes within first year of treatment 5, 8, 9, 11, 20. Our results suggested that the use of first‐year PDC might not reflect well the long‐term adherence behavior, and the longer‐term PDC might capture better the association between PDC and CVD outcomes among the older beneficiaries.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…The attenuation in risk reduction was mainly attributed to the reclassification of 44% (n=20 735) of beneficiaries with intermediate adherence (40–79%) under ≥1 antihypertensive available PDC to ≥80% category using the first‐year PDC. Many studies suggested that the average medication adherence declined significantly over time with the greatest changes within first year of treatment 5, 8, 9, 11, 20. Our results suggested that the use of first‐year PDC might not reflect well the long‐term adherence behavior, and the longer‐term PDC might capture better the association between PDC and CVD outcomes among the older beneficiaries.…”
Section: Discussionmentioning
confidence: 70%
“…Of the 94 617 beneficiaries with ≥80% adherence under ≥1 antihypertensive available PDC, 35 988 (38%) had been reclassified to 40% to 79% category under the average PDC, which might result in the gradual risk reduction under average PDC method. The prevalence of discontinuation or switching to different classes of antihypertensives were common among newly initiated patients, especially during the first year 5, 8, 9, 11, 20. Many of those patients, especially the older patients, might likely be adherent, but discontinued the initial medications because of the side effects or switching to other medications for better blood pressure control, and the average PDC method might misclassify as nonadherent some adherent patients 29.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2,[8][9][10][11][12][13][14][15][16][17][18][19][20] Prior research has consistently found racial differences in medication adherence. [21][22][23][24] The reasons underlying such differences are poorly understood, but are often thought to stem from differences in care access, care quality, and selfmanagement behaviors. 18 As medication non-adherence is associated with poor cardiometabolic risk factor control among patients with diabetes, [8][9][10][11][12][13][14] it has been suggested that differences in medication adherence may be responsible for subgroup differences in risk factor control among patients with diabetes.…”
Section: Introductionmentioning
confidence: 99%